Market institutions and transaction costs influencing trader performance in live animal marketing in rural Ethiopian markets - Jabbar, M.A.; Benin, Samuel; Gabre-Madhin, E.Z.; Paulos, Z. (Oxford University Press, 2008)
In this paper, the hypothesis that performance of trading firms depends on their assets (physical, financial, human capital and social capital) and trading practices is tested with data from a sample of 131 live animal traders in 38 rural Ethiopian highland markets. Most traders used own capital as access to credit, especially formal credit, was limited. The livestock market was characterised by non-standardised products and lack of information in the public domain about supply, demand and prices. Consequently, livestock trading was largely a personalised business though brokers and regular buyers and sellers, a form of social capital, were sometimes used for gathering information, searching buyers/sellers, price negotiation and contract enforcement. Business relationships with these intermediaries were principally based on trust, without strong ethnic, religious or family ties. Although most transactions were conducted in the physical presence of parties, contract violations were common, which were settled mainly through informal means as formal legal systems were either absent or time-consuming. Estimated costs and margins of most recent transactions showed low returns, and losses in some cases. Market levies, transport, travel and feeds were major items of variable cost, with some variation between cattle and small ruminants. Multiple regression analysis showed that traders' financial and human capital and trading practices such as use of brokers and regular suppliers and customers had varying effects on margins and costs of cattle and small ruminant trade. Unstable price, multiple taxes, non-transparent tax system, limited access to credit and weak demand for the quality of the products traded were perceived by traders as major problems of marketing. All the problems were amenable to public policy to improve the market environment and marketing efficiency.